2018
DOI: 10.1159/000492853
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Manifest Stimulative and Protective Effects on Intestinal Barrier Function Through the Inhibition of NLRP3 Inflammasome and Autophagy

Abstract: Background/Aims: Short-chain fatty acids (SCFAs) are the major energy resources of intestinal epithelial cells. It has been reported that SCFAs can repair the dysfunction of intestinal barrier, however, the underlying mechanisms are still not fully understood. Here, we investigated the stimulative and protective effects of SCFAs on intestinal barrier function and the possible mechanisms. Methods: To investigate the effects of SCFAs on intestinal barrier function, the Caco-2 monolayers were exposed to acetate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
225
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(237 citation statements)
references
References 48 publications
9
225
0
3
Order By: Relevance
“…The beneficial effects of dietary fiber on epithelial integrity and intestinal homeostasis are shaped by SCFAs‐NLRP3 inflammasome axis . Herein, we further determined the regulatory effects of LMP on NLRP3 inflammasome in caecum, and found that LMP suppressed NLRP3 inflammasome activation in mice.…”
Section: Discussionmentioning
confidence: 90%
“…The beneficial effects of dietary fiber on epithelial integrity and intestinal homeostasis are shaped by SCFAs‐NLRP3 inflammasome axis . Herein, we further determined the regulatory effects of LMP on NLRP3 inflammasome in caecum, and found that LMP suppressed NLRP3 inflammasome activation in mice.…”
Section: Discussionmentioning
confidence: 90%
“…Large intestine epithelial cells utilize SCFAs, especially butyrate, which supply them by 60-70% with energy and promote strengthening of the mucous membrane barrier [78]. SCFAs also regulate the metabolism of glucose and lipids and im mune functions [177].…”
Section: Connection Of Child Microbiome With Immu Nity and Other Orgamentioning
confidence: 99%
“…Эпителиальные клетки толстой кишки используют КЦЖК, особенно бутират, кото рый на 60-70% обеспечивает их энергией, что способствует укреплению барьера слизистой оболочки [78]. КЦЖК также регулируют мета болизм глюкозы и липидов и иммунную функ цию [177].…”
Section: связь микробиома ребенка с развитием иммунитета и других оргunclassified
“…Butyrate also stabilizes the intestinal barrier function, in particular by influencing hypoxia-inducible factor [9]. In a Chinese study, Feng Y. et al (2018) found that SCFA stimulate the formation of the intestinal epithelial barrier and protect it against damage by lipopolysaccharides, in particular through inhibition of NLRP3 inflammasome and autophagy [10].…”
Section: Introductionmentioning
confidence: 99%